1996
DOI: 10.1038/nm0496-418
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy by skeletal muscle expression of decorin prevents fibrotic disease in rat kidney

Abstract: There are currently no effective therapies for progressive fibrotic diseases. Recent evidence has implicated overproduction of transforming growth factor-beta1 (TGF-beta1) as a major cause of tissue fibrosis. Furthermore, this evidence implies that inhibitors of TGF-beta1 may be clinically useful as antifibrotic agents. The proteoglycan decorin is a known inhibitor of TGF-beta1. In a rat model of glomerulonephritis we have shown that fibrosis is mediated by TGF-beta1. We report here that transfer of decorin cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
273
1
7

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(288 citation statements)
references
References 29 publications
7
273
1
7
Order By: Relevance
“…4,31,32 Additionally, it has also been shown that decorin inhibits TGF-b mRNA transcription and TGF-b protein synthesis. 13,33 However, these functions appear to be highly cell-type specific. In certain cellular systems, decorin blocks the activity of TGF-b, whereas in others its binding augments the bioactivity of the cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…4,31,32 Additionally, it has also been shown that decorin inhibits TGF-b mRNA transcription and TGF-b protein synthesis. 13,33 However, these functions appear to be highly cell-type specific. In certain cellular systems, decorin blocks the activity of TGF-b, whereas in others its binding augments the bioactivity of the cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Moreover, TGF-β antagonism with neutralizing antibodies, soluble TGF-β receptors, and over expression decorin or dominant negative TGF-β receptors has resulted in attenuation of tissue fibrosis can be attenuated in a variety of different tissues including the heart. [25][26][27] Further, expression of Smad7, an endogenous inhibitor of TGF-β induced signaling, attenuates experimentally induced lung and kidney fibrosis. 28,29 Taken together, these observations suggest that sustained activation of TGF-β can lead to pathological tissue fibrosis and/or tissue dysfunction in a variety of organs, including the heart.…”
Section: Tgf-β Signaling and Myocardial Fibrosismentioning
confidence: 99%
“…4,[6][7][8][9] Expression of therapeutic proteins in even a small number of myofibers may be adequate to treat inherited or acquired metabolic disorders, or to induce an immune response in the context of a vaccine. 45,46 Effective methods for muscle gene transfer require vector systems that transduce cells with high efficiency and allow for persistent transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Moreover, the post-mitotic nature and longevity of muscle fibers permits stable expression of transferred genes, even if they are not integrated into chromosomal DNA. 9,10 High level gene expression in a relatively small number of muscle fibers may be adequate to treat inherited or acquired metabolic disorders, or to induce an immune response sufficient for vaccination.…”
Section: Introductionmentioning
confidence: 99%